“It’s almost like they’re trying to hide it": How User-Provided Image Descriptions Have Failed to Make Twitter Accessible - Gleason, Cole; Carrington, Patrick; Cassidy, Cameron; Morris, Meredith Ringel; Kitani, Kris M.; Bigham, Jeffrey P. (The Web Conference, 2019)
To make images on Twitter and other social media platforms accessible to screen reader users, image descriptions (alternative text) need to be added that describe the information contained within the image. The lack of alternative text has been an enduring accessibility problem since the “alt” attribute was added in HTML 2.0 over 20 years ago, and the rise of user-generated content has only increased the number of images shared. As of 2016, Twitter provides users the ability to turn on a feature that allows descriptions to be added to images in their tweets, presumably in an effort to combat this accessibility problem. What has remained unknown is whether simply enabling users to provide alternative text has an impact on experienced accessibility. In this paper, we present a study of 1.09 million tweets with images, finding that only 0.1% of those tweets included descriptions. In a separate analysis of the timelines of 94 blind Twitter users, we found that these image tweets included descriptions more often. Even users with the feature turned on only write descriptions for about half of the images they tweet. To better understand why users provide alternative text descriptions (or not), we interviewed 20 Twitter users who have written image descriptions. Users did not remember to add alternative text, did not have time to add it, or did not know what to include when writing the descriptions. Our findings indicate that simply making it possible to provide image descriptions is not enough, and reveal future directions for automated tools that may support users in writing high-quality descriptions.